Designs for Learning - Taking a Step Forward - Birgitte Holm Sørensen; Staffan Selander; Barbara Wasson; Sofie Wennström (Stockholm University Press, 2016)
'Designs for Learning', established in 2008, is now taking a step forward. During 2015 we have worked with a new publishing format and a new editorial structure, and from 2016 we will be an online, Open Access journal published by Stockholm University Press in (technical) collaboration with Ubiquity Press. The Editorial Board has been extended to a deeper collaboration and a joint editorial structure between Stockholm University, University of Bergen and Aalborg University. These changes enable new possibilities not only for readers, but also for authors and reviewers. Let us explain why.